The commodification of water in Soweto and its implications for social justice - Harvey, Ebrahim (My University, 2009)
Abstract This thesis combines studies in urban, environmental and public sociology and political science. Adequate and unimpeded access to water supply in poor black communities arguably lie at the heart of urban and environmental sociology, social policy and democratic local government. It explores water as a basic and non-substitutable resource and a human right, the countervailing pressures to commercialise and commodify it and the evolving countermovement to these pressures. It also explores the sufficiency of the present water lifeline and the appropriateness or otherwise of prepaid water meters in poor communities and the disempowering and alienating social consequences they appear to have. The contending theses of commodification and decommodification and their underlying social relations is the theoretical framework within which we situate the study. The first section deals with the aim of the study, its rationale, methodology and the theoretical considerations. The second part focuses on the historical and institutional dynamics which both inform and are consequential to water commercialisation and commodification in South Africa. It explores and analyses the technology, ideology and sociology of prepaid water meters in general terms and the specific impacts they have had in Soweto, where the case study is situated. It furthermore critically explores these impacts in relation to the notions of human rights and social justice in the South African context. The epistemic heart of the thesis is the case study, based on a critical examination and analysis of the impacts the limited free water lifeline and the installation of prepaid water meters have had in Phiri, Soweto. It also critically analyses the problems and prospects for resistance to these meters and for developing an anti-commodification countermovement. In conclusion this thesis explores an alternative political, policy and institutional framework which may become necessary in the future if the problems identified as a result of the case study are to be seriously addressed by the service provider, Johannesburg Water, and the City of Johannesburg.